4y-6x-2=0

Simple and best practice solution for 4y-6x-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-6x-2=0 equation:


Simplifying
4y + -6x + -2 = 0
Reorder the terms:
-2 + -6x + 4y = 0
Solving
-2 + -6x + 4y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + -6x + 2 + 4y = 0 + 2
Reorder the terms:
-2 + 2 + -6x + 4y = 0 + 2
Combine like terms: -2 + 2 = 0
0 + -6x + 4y = 0 + 2
-6x + 4y = 0 + 2
Combine like terms: 0 + 2 = 2
-6x + 4y = 2
Add '-4y' to each side of the equation.
-6x + 4y + -4y = 2 + -4y
Combine like terms: 4y + -4y = 0
-6x + 0 = 2 + -4y
-6x = 2 + -4y
Divide each side by '-6'.
x = -0.3333333333 + 0.6666666667y
Simplifying
x = -0.3333333333 + 0.6666666667y

You can always share this solution

See similar equations:

| 3x^2-10x-1=0 | | x^4+8x^2+4x^3+8x=0 | | -16t(t-6)=-204 | | 16*6= | | -16t^2+96t=-204 | | X^2(y+2)=192 | | m*2=6m-9 | | -16t^2+96t+4=-200 | | 864x+1728= | | 0x^2+69x+9= | | 695X^2-21X+63= | | x-3+x-2=17 | | n=8x^3-12x^2y+6xy^2-y^3 | | 2x(2x+1)-4= | | 8x=-4+12n | | 12+3x=28-2*2 | | (x-4)(2x+6)(x^2-9)=0 | | x^4+6x^3+9x^2+4x=0 | | -13x^2+2x+6=0 | | 126000000=0.102x+((1-x)(0.0659)) | | 3x+11=3(x+4) | | 2x^2+5y^2=11 | | 25+5*3-20=2x | | -4(x^2-2x+1)=2x(x-3)-10x^2 | | 2y=4y | | 6x^4+5x^3= | | 3x^2+2x^2+5=0 | | -x^3+3x=2 | | 49x^2-52x+1=0 | | 11x^2-60x+50=0 | | x^2+18x-844= | | x*2+18x-844=0 | | -7x+6x= | | 11x^2+50x-1=0 | | 21x^2+50x-50=0 | | 11x^3+50x-1=0 | | x^2+14x+876=0 | | 5-v=3 | | 7x^2-7x+3=0 | | (x^6+9xy)(-x+4y)= | | 14+9x=8x+16 | | 6b-8=10 | | 3x(2x+9)-14=2x | | m^2+69m-6120=0 | | y=15+40X | | x^2-4x+21=0 | | m^2+69m-680=0 | | 3(x+6)+2(x+3)=64 | | 17-2*5=30+x-24 | | (-2a+7b)-(a+4b)= | | 3(1x-4)=6-1(2x-3) | | 7+4(3x+12)-2=-19 | | 4(p+7)=30 | | 4x-y=-13 | | 3x-20+5=4*20-65 | | 7x(-7)=126 | | 5(2+x)=4(x-1) | | 10=30-p | | 7(x+2)=5x | | (x+26)=(2x+10) | | 2x+65=176 | | 5a-6.1=4a+6.9 | | 255=5x^3 | | 7n-13=4n+35 | | n+6=32 |


Related pages


13x 5x 3equats117t3ln x-23u 4uprime factorization of 315equation step by step solverfactor the expression using gcf1 cos 12x1yfprime factorization of 648simplify 2x 2sin 2x cos 3xgcf of 26derivative of 1 cos2xmath solutions calculator300-226factoring 3x 2 5x-2graph x 3y 6prime factorization of 250k9 solutionsimplify the square root of 180multiplying frac15x 75x4 y4 factordifferentiation of e 2xcos3piwhat is 6.25 as a decimalwww mhcitts com4x 2y 104cosprime factors of 293what is the fraction of 0.875tanx square root of 3x 3-1 factoredfactor 3x 2 4x 1what is 6x squaredroman numerals 1968convert 875 to fraction4cosderivatives of sin2xln 3x derivative294.9greatest common factor of 120hsart1986 in roman numerals2y 3x 13ln x-22sin2x 1roman numeral 19970.1875 as fraction5abcfactoring step by step calculatorfind the prime factorization of 428.25 x 2018p22xy x yroman numerals for 1985x squared factoredleast common multiples calculatorwhat is the derivative of cos 2xderivative of 2lnxlog3 3xderivative ln 3xvx roman numerals7x 12xcos7pi12345 5432110.1.1.310.5.51978 in roman numeralswhat is the lcm ofquad solvergraph 3x 4y 8prime factorization of 525cos pi 2 xsqrt 72roman numerals 1963